Analysis of Student Utilization of Institutional Repositories (Case Study at the University of Mataram) - Ridwan, Ridwan; Furbani, Widiastuti; Mulianto, Rizki Ihsan; Nurwahyuningsih (UPT Perpustakaan UIN Alauddin Makassar, 2025)
This study aims to describe the attitudes and abilities of students at the University of Mataram in utilizing the Institutional Repository as a support tool for academic activities. Employing a descriptive quantitative approach with a correlational research design, data were collected through a closed-ended Likert-scale questionnaire from 100 students selected using purposive sampling. The results indicate that, in general, students exhibit a very positive attitude toward the Institutional Repository, particularly in terms of service flexibility, information diversity, interface design, and the accuracy and completeness of content. Furthermore, students' abilities in accessing, navigating, and utilizing search features—both simple and advanced search—as well as retrieving full-text documents, are categorized as very good. The average scores for all indicators range from 3.15 to 3.69, falling within the